La métrica de Rubén Darío: teoría y praxis - Torre, Esteban (Rhythmica. Revista Española de Métrica Comparada, 2018)
Se lleva a cabo en este trabajo un detenido análisis de la teoría métrica de Rubén Darío, confrontada con la praxis de su propia poesía. Se abordan tres cuestiones fundamentales: la noción de verso libre, las posibles segmentaciones del alejandrino moderno y la aclimatación a la lengua española del hexámetro griego y latino. A close analysis of Rubén Darío’s metrical theory, as set against his own poetic practice, is undertaken in this study. Three fundamental issues are addressed: the notion of free verse, possible segmentations within the modern alexandrine, together with the assimilation of the Greek and Latin hexameter into the Spanish language.